THE EFFECT OF POPULATIONS ADMINISTRATION INFORMATION SYSTEM TECHNOLOGY ON THE PERFORMANCE OF OPERATOR’S POPULATIONS ADMINISTRATION SERVICE THROUGH ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS AN INTERVENING VARIABLE - Purbo, Achmad Jati; Herlambang, Toni; Supeni, Retno Endah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to analyze the effect of populations administration information system technology on the performance of operator’s populations administration service through organizational citizenship behavior as an intervening variable. Method: Research design can be classified as explanatory/confirmatory research. The population to be studied is all employees of population administration service operators in sub-district offices throughout Jember Regency, amount 132 people. Hypothesis testing in this research uses Structural Equation Modeling (SEM) with the WarpPLS statistical tool. Results: Findings of this research state that populations administration information system technology has significant effect on the organizational citizenship behavior and the performance of operator’s populations administration service. Organizational citizenship behavior has significant effect on the performance of operator’s populations administration service. The population administration system has significant effect on employee performance through organizational citizenship behavior. Novelty: This research uses a model of the influence of information system technology on service operator performance by involving organizational citizenship behavior as mediator or intervening. Thus, this model is the answer to the existing research gap related to staff performance.